Quantitative genetics and multifactorial inheritance - Bauman, Lara (Henry Stewart Talks, 2012)
Basic Biometric Model: single locus model, identity states and coefficients, Covariances for relatives, polygenic model, Modeling environment/error, Gene by environment interaction model and example, QTL mapping model, Multivariate model and example